Implementation of School/Madrasah Culture in Improving the Quality of Education Based on the 2020 Education Unit Accreditation Instrument (IASP) at MAN 1 Bandung - Anwar, Miftahul; Nugraha, Mulyawan Safwandy (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2024)
This study aims to analyze the implementation of school/madrasah culture in improving the quality of education based on the 2020 Education Unit Accreditation Instrument (IASP) at MAN 1 Bandung. The research method used is a qualitative descriptive method with a case study approach. Data were collected through observations, interviews, and documentation studies. The results of the study show that the implementation of school/madrasah culture at MAN 1 Bandung has made a positive contribution in improving the quality of education, in accordance with the standards set by IASP in 2020. Factors such as strong leadership, active participation of all related parties, and human resource development are the keys to success in the implementation of school/madrasah culture.